Conspiracy Theories and Their Societal Effects During the COVID-19 Pandemic. Issue 1 (January 2022) - Pummerer, Lotte; Böhm, Robert; Lilleholt, Lau; Winter, Kevin; Zettler, Ingo; Sassenberg, Kai
During COVID-19, conspiracy theories were intensely discussed in the media. Generally, both believing in conspiracy theories (i.e., explanations for events based on powerholders' secret arrangements) and being confronted with a conspiracy theory have been found to predict cognition and behavior with negative societal effects, such as low institutional trust. Accordingly, believing in conspiracy theories around COVID-19 should reduce institutional trust, support of governmental regulations and their adoption, and social engagement (e.g., helping members of risk groups). We tested these predictions in a national random sample survey, an experiment, and a longitudinal study ( N total = 1, 213; all studies were preregistered). Indeed, believing in and being confronted with a COVID-19 conspiracy theory decreased institutional trust, support of governmental regulations, adoption of physical distancing, and—to some extent—social engagement. Findings underscore the severe societal effects of conspiracy theories in the context of COVID-19.